2009
DOI: 10.1093/ntr/ntp074
|View full text |Cite
|
Sign up to set email alerts
|

Measuring cigar use in adolescents: Inclusion of a brand-specific item

Abstract: Results suggest that the current national survey item may not adequately measure cigar use. Accordingly, prevalence of cigar use among adolescents may be greatly underestimated, especially among Black youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 11 publications
5
50
0
Order By: Relevance
“…Brand information was included for little cigars, cigarillos, and bidis; e-cigarettes; dip and snuff; chewing tobacco; snus; and dissolvables, because previous research has shown that it increases validity of estimates. 38,39 Once a respondent endorsed ever using a tobacco product, they were labeled as an ever user of that product at all subsequent waves. For simplicity, ever use will be referred to as "use" from this point forward.…”
Section: Methodsmentioning
confidence: 99%
“…Brand information was included for little cigars, cigarillos, and bidis; e-cigarettes; dip and snuff; chewing tobacco; snus; and dissolvables, because previous research has shown that it increases validity of estimates. 38,39 Once a respondent endorsed ever using a tobacco product, they were labeled as an ever user of that product at all subsequent waves. For simplicity, ever use will be referred to as "use" from this point forward.…”
Section: Methodsmentioning
confidence: 99%
“…For current use of a product, participants were asked the following: "Which of the following products have you used in the past 30 days (select all that apply)." Following established methods to increase validity of reporting (Terchek, Larkin, Male, & Frank, 2009;Trapl et al, 2011), examples of usual brands of LCCs (i.e., Black and Milds, Swisher Sweets, and Phillies) and e-cigarettes (blu, NJOY) were included in the question to further assist with the query.…”
Section: Tobacco Use Outcomesmentioning
confidence: 99%
“…youth (Connoly & Alpert, 2008;Page & Evans, 2004;Singer et al, 2007;Terchek, Larkin, Male, & Frank, 2009). The FSPTCA does not give the FDA authority to regulate cigar marketing.…”
Section: Smoking Of Cigarillos and Cigarettesmentioning
confidence: 99%